Performance of Ni-Ce oxide black protective coatings produced via photo-assisted potentiodynamic deposition - Zizhou Qin; Yumeng Yang; Yang Zhang; Benfeng Zhu; Jiao Liu; Li Jiang; Ming Liu; Zhiji Deng; Guoying Wei (Applied Surface Science Advances)
Black coatings have garnered considerable interest from researchers due to their distinctive properties and wide-ranging applications. This study investigates the effects of illumination and deposition potential on the properties of Ni-Ce oxide black protective coatings and elucidates the possible reasons for the changes in hydrophobicity. The results indicate that illumination accelerates the coating deposition process. Under illumination, the coating thickness increased from 3.27 μm to 5.44 μm, and the surface roughness rose from 0.38 to 0.84. The absorption rate in the UV–visible region and emission properties of the coating deposited with photo illumination reached up to 95 % and 0.87, respectively. Moreover, by manipulating of the deposition potential range, precise control over the coating’s thickness and roughness was achieved, enabling the optimization of its absorption and emission properties. The optimal deposition potential range was found to be between 0 and -1.4 V. Illumination conditions also play a crucial role in the rate of change of the water contact angle. The contact angle of water increased from 19.2° to 132° as the placement time increased. This significant enhancement in the water contact angle variation could be attributed to the adsorption of hydrocarbons from the ambient air. This research provides a promising methodology for the development of black coatings with exceptional absorptivity and emissivity, which may find applications in the aerospace industry and precision optical instruments.